The Dispute and Sensitive Atmosphere in Difficult Daughters - Devi, J.Brindha; Manimehala; M.D, Shreedharan; M, Jeganathan (International Journal of Psychosocial Rehabilitation, 2018)
Daughters suffer in silence but are not able to share their private sorrows with their mothers theabsence of lack of mother’s sympathetic shoulders at home forces these daughters to look for sympathy outsidewhich leads to deception. Daughters become Vulnerable to outside influences. The sense of belonging that is theessence of a good relationship is found sadly missing from this relationship which is most vital in the life of awoman.DifficultDaughtersisthefirstnovelofManjuKapur.AsManjuKapursays:“Ihadtorewritet hebookeighttimes over seven years. And each time I thought I had finished the book” (106). UrvashiButalia of Kali forwomen was struck by the simplicity of ManjuKapur’s writing style: “There is no gimmickry in the language, aswe see in some other books” (106). The novelist MukulKesavan comments Difficult Daughters as: “a first raterealistic novel about a daughter’s reconstruction of her troubled past, hinging on her mother’s story”